Efektivitas Pendampingan Belajar Siswa Dalam Mengatasi Kesulitan Orang Tua Masa Pandemi Covid-19 - Siti Zulaikha; M. Trihudiyatmanto (J-PEMAS - Jurnal Pengabdian Masyarakat, 2021)
The policy of studying at home or studying online is a new problem in the field of education. The difference is very clearly seen due to the lack of readiness of parents in assisting children, the limited facilities provided by parents to children, and the lack of material explanations given by teachers to students. For this reason, UNSIQ Thematic KPM 2021 students participate in community life by providing direction and learning assistance for students in Lipursari Village both online and face-to-face.This research focuses on identifying the role and function of learning assistance in increasing the enthusiasm for learning of students in Lipursari Village during the Covid-19 pandemic. The data were collected from the impressions and messages given by the students participating in the learning mentoring until the learning mentoring process ended. Then the data is analyzed and then narrated. The existence of learning assistance carried out by UNSIQ 2021 Thematic KPM students can have a positive influence on students. This learning assistance can help students who have difficulty studying at home both in understanding learning materials and adding other knowledge and also provide good results for the student learning process.